Marco Gonzalez, Ambergris Caye, Belize: A geoarchaeological record of ground raising associated with surface soil formation and the presence of a Dark Earth. (January 2017) - Macphail, Richard I.; Graham, Elizabeth; Crowther, John; Turner, Simon
Abstract: Marco Gonzalez, on the south-west end of the island of Ambergris Caye, Belize, has well-preserved Maya archaeological stratigraphy dating from Preclassic times (ca. 300 B.C.) to the Late Classic period (ca. A.D. 550/600 to 700/760). Although later occupations are recorded by house platforms and inhumations (Terminal Classic to Early Postclassic), and use of the site continued until the 16th century A.D., intact stratigraphy is rare in these cases owing to a greater degree of disturbance. Nonetheless, understanding site formation entails accounting for all processes, including disturbance. The site's depositional sequence—as revealed through soil micromorphology and chemistry and detailed here—has yielded critical information in two spheres of research. As regards archaeology and the elucidation of Maya activities on the caye over time, soil micromorphology has contributed beyond measure to what we have been able to distinguish as material remains of cultural activity. Detailed descriptions of the nature of the material remains has in turn helped us to clarify or alter interpretations based on artefacts that have been identified or sediments characterised according to traditional recovery techniques. The other major sphere in which soil micromorphology and chemistry play a critical role is in assessment of the environmental impact of human activity, which enables us to construct and test hypotheses concerning how the site formed over time; what materials and elements contributed to the character of the sediments, especially in the formation of a specific Maya Dark Earth type that is developed from carbonate rich deposits; and how the modern surface soils acquired the appearance of a Dark Earth, but essentially differ from them. In terms of agricultural soil sustainability, the Marco Gonzalez surface soil is neo-formed by a woodland vegetation drawing upon the nutrients and constituents present in both the Dark Earth and underlying better preserved stratified deposits. Highlights: Site formation processes. Ground-raising from Maya industrial activity and waste accumulation. Sponge spicule-rich clays from mudflats used as lime plaster floor temper and as a brine source in salt production. Late Classic marine inundation event.